ANALYSIS OF THE MAIN CHARACTERS IN STORYLINE THE FILM “NANTI KITA CERITA TENTANG HARI INI” - muji Endah palupi; sri arfani (STIBA IEC JAKARTA, 2023)
The purpose of this study is to Analyze of The Main characters in Storyline The Film